PENGUATAN KELEMBAGAAN BUMDES DALAM MENINGKATKAN PENDAPATAN ASLI DESA DI DESA LABUH AIR PANDAN KECAMATAN MENDO BARAT - Hanita, Mia; Handini, Widya (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2023)
Research emerged on basic problems that often occur in the process of strengthening BUMDes in increasing PADes in Labuh Air Pandan Village. In general, the problems currently faced by BUMDes in Labuh Air Pandan Village include that BUMDes officials have not fully understood their functions and roles in BUMDes institutional management, and still need assistance to be able to accommodate developing economic activities in Labuh Air Pandan Village. Seeing the phenomenon of the lack of human resources owned by Labuh Air Pandan Village, and balanced with institutional management that has not been optimally carried out by the BUMDes of Labuh Air Pandan Village. This study uses a quasi-qualitative method which explains in detail how to strengthen BUMDes in increasing PADes in Labuh Air Pandan Village using primary and secondary data, namely interviews, observation and documentation. The analysis technique uses a triangulation technique that looks at the process from collection to drawing conclusions. Based on the results of the research, the authors conclude that: so far institutional strengthening in Labuh Air Pandan Village-Owned Enterprises has generally been good but not optimal. This is shown by several strengthening efforts such as the development of human resources, organizational and institutional strengthening, but even though these efforts are optimized for PADes it is still not optimal, this is influenced by the human resource factor and obstacles as network problems found